Ultrastructural studies of abaxial and adaxial sides of in vivo and in vitro leaves in Sainfoin (Onobrychis viciifolia) - Mat Taha, R. (2014)
Leaf specimens of both types of in vitro and in vivo growth were evaluated in sainfoin (Onobrychis viciifolia). It was found that different resistance strategies of Sainfoin can be assessed based on stomata, epicuticular waxes, convex cell, trichomes and calcium oxalate crystals function.